Pengaruh Penggunaan Media Poster Terhadap Motivasi Belajar Siswa Mata Pelajaran IPS Kelas VIII - Dwinita Meilia Sari; Tontowi Amsia; Muhammad Basri (PESAGI (Jurnal Pendidikan dan Penelitian Sejarah), 2019)
The purpose of this study was to determine the effect of increasing the use of posters on the learning motivation of class VIII students on social studies subjects at SMP Negeri 17 Bandar Lampung Academic Year 2017/2018. Sample research of class VIII students using the True-Experimental Designs. Data on student learning motivation was obtained using a questionnaire consisting of 16 items of statements. Data collection techniques used were observation, interviews, questionnaires, documentation and literature. Data analysis techniques used qualitative percentage formulas. Based on the results of data analysis that the use of poster learning media has an effect on increasing student motivation in social studies namely the first test experimental class is categorized as 1 Highly Motivated student 3% percentage, 20 students categorized Motivated percentage 69%, 8 people categorized as Less Motivated percentage 28, the second test 10 people categorized as Very Motivated percentage 34%, 17 people categorized Motivated percentage 59%, 2 people categorized as Less Motivated percentage 7%.Tujuan penelitian untuk mengetahui adanya pengaruh peningkatan penggunaan poster terhadap motivasi belajar siswa kelas VIII pada mata pelajaran IPS di SMP Negeri 17 Bandar Lampung Tahun Ajaran 2017/2018. Sampel penelitian siswa kelas VIII menggunakan desain True-Experimental Designs. Motivasi belajar siswa diperoleh menggunakan angket yang terdiri dari 16 butir pernyataan. Teknik pengumpulan data yang digunakan adalah observasi, wawancara, angket, dokumentasi dan kepustakaan. Teknik analisis data secara kualitatif dengan menggunakan rumus presentase. Hasil analisis data bahwa penggunaan media pembelajaran poster berpengaruh terhadap peningkatan motivasi belajar siswa pada mata pelajaran IPS yaitu test pertama kelas eksperimen dikategorikan 1 siswa Sangat Termotivasi presentase 3%, 20 siswa dikategorikan Termotivasi  persentase 69%, 8 orang dikategorikan Kurang Termotivasi persentase 28, test kedua 10 orang dikategorikan Sangat Termotivasi presentase 34%, 17 orang dikategorikan Termotivasi presentase 59%, 2 orang dikategorikan Kurang Termotivasi persentase 7%.Kata kunci: media poster, motivasi belajar, pengaruh